Computer science and computer simulation in preparation of the future architects - Бірілло, І. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The article deals with the problem of the relevance of training of future architects, the role of discipline «Computer science and computer simulation» in preparing future professionals аrchitects. The objectives of the course have been defined and learning outcomes highlighted. Interdisciplinary connections of the discipline in accordance with the curriculum of the National Aviation University (NAU) have been established. They determine the content and rational planning of training to meet the needs, modern requirements, contribute to the improvement of the educational process. The structure, practical orientation, the importance of studying the course of computer science and computer simulation for the formation of architecture students’ basic informatics competencies with the premise of the subsequent formation of their professional competence in informatics have been disclosed